2018
DOI: 10.1073/pnas.1802567115
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate-activated BK channel complexes formed with NMDA receptors

Abstract: The large-conductance calcium- and voltage-activated K (BK) channel has a requirement of high intracellular free Ca concentrations for its activation in neurons under physiological conditions. The Ca sources for BK channel activation are not well understood. In this study, we showed by coimmunopurification and colocalization analyses that BK channels form complexes with NMDA receptors (NMDARs) in both rodent brains and a heterologous expression system. The BK-NMDAR complexes are broadly present in different br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 64 publications
8
57
3
Order By: Relevance
“…Kcnma1 encodes the large-conductance calcium-activated potassium channel, subfamily M, alpha member 1 (BK channel) pore-forming alpha subunit, which is involved in neuronal excitability and plasticity, and has been associated with neurological and psychiatric disorders, including epilepsy autism and Alzheimer’s. While the activation of presynaptic BK channels decreases glutamate release 54 56 , the activation of postsynaptic BK, which couples to GluN1, suppress NMDA-potentiated evoked excitatory postsynaptic potentials (EPSP) 57 . Our results suggest that early upregulation of Kcnma1 channels might provoke sustained hypoactivity of excitatory pathways in the hippocampus (reducing glutamate release, and suppressing NMDA receptors).…”
Section: Discussionmentioning
confidence: 99%
“…Kcnma1 encodes the large-conductance calcium-activated potassium channel, subfamily M, alpha member 1 (BK channel) pore-forming alpha subunit, which is involved in neuronal excitability and plasticity, and has been associated with neurological and psychiatric disorders, including epilepsy autism and Alzheimer’s. While the activation of presynaptic BK channels decreases glutamate release 54 56 , the activation of postsynaptic BK, which couples to GluN1, suppress NMDA-potentiated evoked excitatory postsynaptic potentials (EPSP) 57 . Our results suggest that early upregulation of Kcnma1 channels might provoke sustained hypoactivity of excitatory pathways in the hippocampus (reducing glutamate release, and suppressing NMDA receptors).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that BK channels in mature dentate granule cells form complexes with NMDA receptors [27], and this structural and functional coupling might also occur in immature neurons. In line with this, we found a robust BK current after local NMDA or glutamate application onto the recorded immature neurons, but ambient glutamate levels were not able to open NMDARs in our experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that ethanol can activate both clustered and diffuse SLO-1 channels but only clustered SLO-1 channels are relevant to ethanol sensitivity due to their coupling with calcium channels that mediate behavioral sensitivity to ethanol. It has been reported that BK channels are functionally coupled with a wide variety of calcium channels 2327 , which localize to distinct subcellular compartments, including pre- and post-synaptic sites, the ER, and muscle excitation sites 28,29 . Although clustered and diffuse SLO-1 channels both increase potassium efflux in response to ethanol, only clustered SLO-1 channels lead to an inhibition of behaviorally-relevant calcium channels, thereby causing sedation at the behavioral level.…”
Section: Discussionmentioning
confidence: 99%